The problem of consolidating the values of citizenship education among the learners - Benkhadir , Nabil (Social Empowerment Journal, 2021)
Citizenship education is one of the topics that are of great importance within the educational system, due to its effective role in consolidating the values ​​of true citizenship among young people, and the consequent improvement in their behavior and raising their awareness of the need to cling to their rights and abide by their duties. This study constitutes an attempt to understand the role of citizenship education in developing learners’ behavior with the possibility of consolidating their human rights principles in them, and thus contributing to building their balanced personality imbued with patriotism, and making them good citizens and positive actors within society. The study reached a basic conclusion that it is the family and educational institutions that assume the primary role in perpetuating the values ​​of citizenship among the learners, provided that the various difficulties and obstacles that prevent this are overcome.